A comparison of retention rates of brackets with thermally-cured and light-cured custom bases in indirect bonding procedures - Miles Peter G. (Sciendo, 2000)
This study compared the retention rates of thermally-cured (TC) and light-cured (LC) custom bases attached to metal mini-diamond brackets and clear Spirit MB brackets, when used in indirect bonding procedures. The custom base comprised either the light-cured or thermally-cured material attached to the bracket base and prepared in the laboratory, the whole unit later being bonded to the natural teeth. Thirty consecutively treated patients had fixed appliances fitted in both arches, with Spirit MB brackets on the maxillary anterior teeth, and metal brackets on the maxillary posterior and all mandibular teeth. All brackets were bonded using either the LC or TC method. All procedures and treatment was by the same operator, using identical techniques. Observation was for six months. All bonding failures were recorded. The results indicated no significant differences in the retention rates of either of the custom-base materials when used with metal brackets. However, the Spirit MB brackets exhibited a significantly higher bonding failure rate when a TC custom base was used. It was therefore concluded that either material could be used in the indirect bonding of metal brackets, and that LC custom bases should be used in the indirect bonding of Spirit MB brackets.